Differences in the contractile properties of the knee extensor and flexor muscles in professional road cyclists during the season - Garcia-Garcia, O.; Cancela-Carral, J. M.; Martinez-Trigo, R.; Serrano-Gomez, V. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to establish reference values of tensiomyography (TMG) in professional road cyclists and to examine how the planned periods of the Season produce differences in the muscles: vastus medialis (VM), vastus lateralis (VL), rectus femoris (RF), and biceps femoris (BF), and to determine how these differences may depend on each cyclist, the assessed muscle, and the side of the body. Ten professional road cyclists (27.5 ± 5.5 years; 178.2 ± 7.8 cm; 65.6 ± 5.46 kg; 72.1 ± 3.7 ml/kg/min VO2; 6 ± 0.4 W/kg) were assessed by TMG, in microcycle recovery, at 2 moments of periods during the season: preparation period (PP) and competition period (CP). Student's t contrast for paired groups, Cohen's d effect sizes, and a repeated measures analysis of variance (ANOVA) was applied. We did not find significant differences (p < 0.01) between the lower limbs. The results showed a significantly large increment between the time contraction (TC) values of the PP and CP in the muscles VM (28.7 ± 5.5 vs. 40.6 ± 14.4 milliseconds; 41.4%, p < 0.05, d = 1.1), VL (28.3 ± 4.9 vs. 40.6 ± 10.2 milliseconds; 43.4%, p < 0.05, d = 1.53), and RF (35.9 ± 6.9 vs. 45.9 ± 16.2 milliseconds; 27.8%, p < 0.05, d = 0.8). Nevertheless, TC of the BF presents a significantly large decrease in the CP (35.9 ± 9.9 vs. 28.2 ± 5.2 milliseconds; -21.4%, p < 0.05, d = 0.97). Radial muscle displacement (DM) values are slightly lower during the CP, but the difference is not significant. ANOVA confirmed that these differences depend on the evaluated muscles (TC p = 0.02; DM p = 0.001) and on the cyclists (TC p = 0.001; DM p = 0.001) and does not depend on the side of the body. In conclusion, the TC values during the Season show marked differences between the knee extensors (large increased) and the knee flexor (large decreased). The DM has not changed significantly, keeping the muscular and tendon stiffness.